SDS-PAGE and numerical analysis of Candida albicans from human oral cavity and other anatomical sites - Rodrigues, Cristina Crespo; Höfling, José Francisco; Gomes Boriollo, Marcelo Fabiano; De Oliveira Rodrigues, Janaina Aparecida; De Azevedo, Ricardo Antunes [UNESP]; Gonçalves, Reginaldo Bruno; Gomes, Luiz Humberto [UNESP]; Almeida Tavares, Flávio César [UNESP] (FapUNIFESP (SciELO), 2004)
The aim of the present research was to evaluate the protein polymorphism degrees among forty-eight C. albicans isolates from fourteen anatomical sites of clinical patients by polyacrylamide gel electrophoresis (SDS-PAGE) and numerical analyzes, in order to identify subspecies and their similarities in some infectious niches. Cell cultures were grown in YEPD medium, collected by centrifugation, and washed in cold saline solution. The whole-cell proteins were extracted by cell disruption using glass beads and submitted to SDS-PAGE technique. After electrophoresis, the protein bands were stained with coomassie-blue and analyzed by statistics package NTSYS-pc version 1.70 software. Similarity matrixes and dendrograms were generated by application of similarity coefficient of simple matching and UPGMA algorithm, respectively. The results obtained showed several C. albicans subtypes and their similarity degrees (80% to 100%). Such data showed that same patients may be infected by two or more C. albicans subtypes in certain anatomical sites (i.e. only in oral cavity of immunocompromised patients, blood, or tracheal secretion), or yet, two or more patients can be infected in identical anatomical sites (i.e. bronchial washing, urine, oral cavity, tracheal secretion, vaginal secretion, and healthy saliva) with a same C. albicans subtype. However, two or more patients also can show infections in corresponding sites (i.e. oral cavity of immunocompromised patients, blood, oropharyngeal secretion, oral cavity, tracheal secretion, vaginal secretion, and healthy saliva) by different C. albicans subtypes. Besides, two or more patients also can be infected with identical or different C. albicans subtypes in different anatomical sites (i.e.1. identical subtypes in vaginal secretion, tracheal secretion, and urine; abdominal secretion and spittle; drainage and oral cavity; catheter and healthy saliva - i.e.2. subtypes different in bronchial washing, oropharyngeal secretion, pulmonary secretion, oral cavity of immunocompromised patients, and blood). Complementary studies involving C. albicans sample isolated from several anatomical sites of immunocompetent or immunocompromised patients (before, during and after specifics therapies) and their families or hospital workers must be done in order to establish the sources of C. albicans colonization. The whole-cell proteins profile performed by SDS-PAGE associated with computer-assisted numerical analysis may provide preliminary criteria for taxonomic and epidemiological studies of such microorganisms.
Keywords: C. Albicans; Human anatomical sites; Numerical analyzes; SDS-PAGE